Fiber optic white light interferometer for areal surface measurement. (19th November 2019) - Zhang, Guofeng; Yang, Shuming; Fluegge, Jens; Bosse, Harald
Abstract: White light interferometers (WLI) are extremely powerful tools in the context of areal surface topography instrumentation. With lateral scanning mechanisms, larger objects with trans-scale structures are also measurable. However, the existing commercial WLIs are usually only applicable for off-line measurements in the laboratory. This paper presents a flexible WLI, in which the light source and the vertical scanning mechanism are separated from the interference probe using fiber-optic components. As a result, the interference probe is more compact, and portable for on-machine measurement. Meanwhile, a comprehensive algorithm that combines the improved gravity center method and phase-shifting technique is proposed for signal processing, which can balance computation time and noise robustness. The simulation results show the effectiveness by comparing with the traditional white light scanning interferometry methods. A 1000 nm step height standard was used as a test specimen to evaluate the proposed system and algorithm. The experimental data show that the measurement results are basically in good agreement with the calibrated value.